Analysing Repeat Alms Donation Behavior via Digital Platform - Erlang Ivannanda Hidayatullah; Lintang Titian Purbasari (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to analyze sustainable behavior in paying alms through a digital platform. The data was collected using an online questionnaire with a sample of 50 millennial Muslims in Surabaya who had made alms payments through a digital platform. This study uses a quantitative approach and analysis using multiple linear regression. The sampling technique used is purposive sampling. The results of this study indicate that religiosity, perceived ease of use, and e-satisfaction have a positive effect on the sustainable behavior of millennial Muslims in paying alms through digital platforms. The perceived ease of use variable has a small effect on the intention of repeated donations, it is possible that this is due to the lack of internet network in the area and the insufficient balance of funds in the application. Suggestions for further research is to use a qualitative approach in order to obtain more accurate information and use other variables that are more supportive and relevant.